Students Motivation and Learning Output at Permodalan Koperasi Course of Program Studi Pendidikan Ekonomi through Application of Gagne’s Cognitive Model - Ekawarna, Ekawarna; Irwan, Irwan (Makara Human Behavior Studies in Asia, 2010)
The purpose of this research are to (1) increasing result of student learning in Program Studi Pendidikan Ekonomi Jurusan PIPS FKIP Universitas Jambi at Permodalan Koperasi course in order to obtain minimum average score "B+" as instructional effects which created by the lecturer; (2) increasing motivation of student learning as nurturant effects. This is a descriptive-analitical type of research, using classroom action research. Classroom action research was set for 40 students. Research was designed for 3 cycles, each cycle includes phases of: planning, implementation of action, observation and evaluation, analysis and reflection, and revision for plan and execution of the next cycle. The result indicates that after cycle III the mean result of learning output reaches 75.67, which mean that average level of student competency after cycle III has reached 75.67%. Motivation of student learning reaches highest criterion that is 87%. There is significantly positive correlation between motivation and learning output. If means students who have high motivation to learn will have high result of learning output. As a conclusion, the learning process by applying the cognitive learning model of Robert Gagne at Permodalan Koperasi course Program Studi Pendidikan Ekonomi Jurusan PIPS FKIP Universitas Jambi can increase students motivation and learning output.